Continuous versus Cyclic Progesterone Exposure Differentially Regulates Hippocampal Gene Expression and Functional Profiles - Liqin Zhao; Todd E. Morgan; Zisu Mao; Sharon Lin; Enrique Cadenas; Caleb E. Finch; Christian J. Pike; Wendy J. Mack; Roberta Dı́az Brinton (2012)
This study investigated the impact of chronic exposure to continuous (CoP4) versus cyclic progesterone (CyP4) alone or in combination with 17β-estradiol (E2) on gene expression profiles targeting bioenergetics, metabolism and inflammation in the adult female rat hippocampus. High-throughput qRT-PCR analyses revealed that ovarian hormonal depletion induced by ovariectomy (OVX) led to multiple significant gene expression alterations, which were to a great extent reversed by co-administration of E2 and CyP4. In contrast, co-administration of E2 and CoP4 induced a pattern highly resembling OVX. Bioinformatics analyses further revealed clear disparities in functional profiles associated with E2+CoP4 and E2+CyP4. Genes involved in mitochondrial energy (ATP synthase α subunit; Atp5a1), redox homeostasis (peroxiredoxin 5; Prdx5), insulin signaling (insulin-like growth factor I; Igf1), and cholesterol trafficking (liver X receptor α subtype; Nr1h3), differed in direction of regulation by E2+CoP4 (down-regulation relative to OVX) and E2+CyP4 (up-regulation relative to OVX). In contrast, genes involved in amyloid metabolism (β-secretase; Bace1) differed only in degree of regulation, as both E2+CoP4 and E2+CyP4 induced down-regulation at different efficacy. E2+CyP4-induced changes could be associated with regulation of progesterone receptor membrane component 1(Pgrmc1). In summary, results from this study provide evidence at the molecular level that differing regimens of hormone therapy (HT) can induce disparate gene expression profiles in brain. From a translational perspective, confirmation of these results in a model of natural menopause, would imply that the common regimen of continuous combined HT may have adverse consequences whereas a cyclic combined regimen, which is more physiological, could be an effective strategy to maintain neurological health and function throughout menopausal aging.